Implementation of the Merdeka Curriculum in the Society 5.0 Era - Abidin, Zainal (Program Pascasarjana Institut Agama Islam Darullughah Wadda'wah Bangil Pasuruan, 2025)
Global challenges related to the digital revolution in the Society 5.0 era drive the need for innovation within the national education system, including the implementation of the Merdeka Curriculum in Indonesia. The aim of this study is to analyze the factors and stages influencing the successful implementation of the Merdeka Curriculum within the context of Society 5.0, as well as to identify barriers and opportunities. This research employs a mixed-method approach, collecting data through interviews, classroom observations, and document analysis at three secondary schools in Bangil, Pasuruan over a period of three months. The findings show that the implementation of the Merdeka Curriculum is appreciated for its flexibility, especially in developing innovative learning and utilizing technology, which aligns with theories of adaptive leadership and resource management. However, some challenges such as lack of facilities, training, and community perceptions remain main obstacles, resulting in variations in student learning outcomes across schools. These findings emphasize the need for investments in infrastructure and training, as well as the importance of ongoing collaboration and evaluation to improve implementation effectiveness. The contribution of this study is to provide an empirical basis for developing sustainable and innovative curriculum strategies in the Society 5.0 era.